The reliability and validity of the driving behaviour, road crash involvement, workingcommute (MyDRIVE) questionnaire among Malaysian medical doctors - Abdul Rashid, Aneesa; Nordin, Rusli; Ismail, Khairil Idham; Qureshi, Ahmad Munir; Ismail, Ahmad Filza; Wong, Shaw Voon; Devaraj, Navin Kumar (Universiti putra Malaysia, 2023)
Introduction: The Driving Behaviour, Road Crash Involvement, Working Commute (MyDRIVE) questionnaire was developed to assess medical doctors’ experience with road crash involvement. The objective of this research was to validate the driving behavioural component of MyDRIVE for medical practitioners in Malaysia. Method: This was a multi-stage study involving item specification, domain specification and domain assessment. Following item pools among the experts, Malaysian Medical Association (MMA) members and their contacts who are partially or fully registered with the Malaysian Medical Council (MMC) were surveyed via an online questionnaire between April 2020 and May 2021. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) was done with 150 participants and 824 participants, respectively on separate analysis to ensure the factor validity. We examined the standardized loadings, AVE and CR to determine the convergent validity. The discriminant validity was tested through the Fornell-Larcker matrix. Reliability analysis was performed through Cronbach alpha and composite reliability. Results: EFA resulted in reduction of items from 44 items to 23 items with six constructs. Composite reliability (CR) revealed all domains have a CR of above 0.7, except for Driving Under Alcohol Influence (DAI) (0.605). The remaining factors are Distracted Mind & Negative Emotion (DMNE) (0.843), Safe Driving Habit (SDH) (0.862), Fatigue Driving (FD) (0.903), Recreational & Prescribed Driving (RPD) (0.748), and Driving Under Influence of Caffeine (DCI) (0.836). For discriminant validity the square root of AVE for all constructs were greater than its correlations with other latent constructs. Conclusion: Our study finds the driving behavioural component of the MyDRIVE questionnaire among the Malaysian medical doctors to have good reliability and validity. Future studies should consider using MyDRIVE’s driving behaviour component to assess driving behaviour among doctors.